RESEARCH OF THE MOVEMENT OF FIBERS IN THE CONFUSION BETWEEN THE AIR CHANNEL AND THE ROTOR IN A PNEUMO-MECHANICAL SPINNING MACHINE - korabayev, sherzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. In this paper, we conducted research based on a new experimental approach to describe the airflow in a rotor-spinning machine experimentally. This article studied the movement of fibers in the air channel and the rotor in the pneumomechanical spinning machine. In this case, the airflow speed was changed from 5 m/s to 30 m/s. Differential equations of motion along the OX and OY axis were created considering the air resistance. Methods. When determining the movement of fibers in a conical channel, the total speed was divided into components, constant values were found, and general equations of motion were derived. Also, time-dependent graphs of the movement of fibers in a conical channel along the OY axis on different surfaces, and time-dependent graphs of the movement along the OY axis at different speeds were obtained. Results. The results of the study showed that the movement of fibers in the conical channel along the OY axis is a time-dependent graph on different surfaces S1=14,51, S2=12,56, S3=10,75, in the channel time-dependent graphs at a speed of 30m/s 25m/s 20 m/s were obtained. Conclusion. The results of the study showed that when the time-dependent graph of the movement of the fibers in the conical channel along the OY axis was obtained on different surfaces S1=14,51, S2=12,56, S3=10,75, the fibers on the small surface were straight. When the velocity is high, the time-dependent graph of the speed of 30m/s 25m/s 20 m/s in the channel was obtained at high speed. Keywords: pneumomechanical spinning, separator, air channel, fiber, chamber, cone.